Indian village revisited : Ranawaton-ki-Sadri (1955-2005) - Chauhan, Brij Raj, 1927-2009; Atal, Yogesh; Institute of Social Development, Udaipur (Udaipur : Institute of Social Development ; Jaipur : Rawat Publications, 2018)
Social conditions in Ranawaton-ki-Sadri, village in Rajasthan; a study.
Includes bibliographical references (pages 175-177) and index.
Keywords: Village-microcosmic changes; Urbanization and modernization; Ranawaton-ki-Sadri (India) -- Social conditions